UNVEILING THE PROFIT MOTIVE: A CRITICAL EXAMINATION OF PRIVATE HOSPITALS’ EXPLOITATION IN PATIENT DIAGNOSIS AND TREATMENT - Khalid Al Sharyayh, HasseinAli AlbainAlsulaiman, Nasser Mesfer Ali Alyami , Hamad Mohammed Yahya Al khamsan, Hussein Saleh Ali Al Yami, Mohammad Hammad Mohammad Alyami, Yusosef Salem Mohammed Alyami (Chelonian Research Foundation, 2023)
This article critically examines the profit-driven practices of private hospitals, highlighting the implications for patient care, especially in terms of diagnosis and treatment. With the privatization of healthcare, private hospitals have become prominent players, often associated with advanced medical technologies and superior care. However, this shift raises significant concerns about the exploitation of patients through overdiagnosis, overtreatment, and inflated medical costs. Through a comprehensive review of case studies, regulatory frameworks, and the ethical dilemmas faced by healthcare professionals, this article sheds light on the complex dynamics between profit motives and patient welfare. It also explores the role of insurance in perpetuating high-cost treatments and the impact of financial incentives on edical decision- making. The article calls for a reevaluation of healthcare priorities, advocating for reforms that balance the benefits of private healthcare innovation with the need for accessible and ethical patient care. By comparing global perspectives, it suggests potential pathways towards a more equitable healthcare model that integrates the strengths of both private and public systems. Keywords: Private healthcare, Patient exploitation, Profit motive, Overdiagnosis, Overtreatment, Healthcare ethics, Medical costs, Healthcare reform, Insurance dynamics, Public vs. private healthcare